The Effect of Sintering Temperature on The Adhesion Quality of Hydroxyapatite on Porous Tantalum for Cancellous Bone Implant Application - Saputra, Rizal Adi; Sukmana, Irza; Tarkono; Sugiri, Agus; Syazwani, Nur; Djuansjah, Joy (Jurnal Inovasi Teknologi, 2024)
Porous tantalum has been recently recognized as a conventional orthopedic implant for bone substitute applications besides stainless steel, cobalt-chromium, titanium, and other metallic alloys. Porous tantalum has excellent mechanical and osseointegration properties similar to cancellous bone structure. To optimize the utilization, the dip coating technique was applied to coat porous tantalum with hydroxyapatite (HA). X-ray diffraction (XRD) and scanning electron microscopy (SEM) techniques investigate the coating characterization. HA is a bioceramic material that used for bone substitutes due to its chemical and structural similarity to bone minerals. Coated porous tantalum requires the sintering process of porous tantalum to adhere to HA. During the sintering process, various temperatures (650°C, 750°C, 850°C, 950°C, and 1100°C) were used to determine the optimum temperature for porous tantalum coated with HA. The heating rate is 1°C/1 min and the holding time is 60 minutes. The result shows that the optimum temperature of HA-coated porous tantalum is at 850°C. The morphology structure of the HA-coated porous tantalum shows that the adhesion between porous tantalum and HA is in good condition. The element in the HA-coated porous tantalum shows that the existence of HA is high.